2024
DOI: 10.1002/leap.1606
|View full text |Cite
|
Sign up to set email alerts
|

ORCID identifier adoption in Spanish scholarly communication: A macro and micro level perspective

María Bordons,
Luz Moreno‐Solano,
Borja González‐Albo

Abstract: Personal identifiers have become essential for unambiguously identifying authors and their scholarly output. One of the top personal identifiers is ORCID because of its open, cross‐national, cross‐disciplinary nature. This study analyses ORCID adoption at two levels: (a) Spanish scientific articles in Web of Science (WoS), to explore ORCID presence in articles; and (b) European Research Council (ERC) grant recipients who are affiliated with a Spanish host institution, to explore the prevalence of ORCID‐iDs, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…This suggests that while ORCID is a valuable tool, its potential is not being fully realized due to partially completed and private profiles (Wang et al, 2024). Besides, as ORCID is recognized as potentially playing a crucial role in preventing authorship fraud (Teixeira da Silva, 2023), the interoperability with other databases and automatic updating of profiles by other entities in the research ecosystem (such as institutions, publishers, and funders) could significantly improve the completeness of metadata, thereby increasing the reliability of ORCID to carried out this type of studies (Teixeira da Silva, 2022;Bordons et al, 2024).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that while ORCID is a valuable tool, its potential is not being fully realized due to partially completed and private profiles (Wang et al, 2024). Besides, as ORCID is recognized as potentially playing a crucial role in preventing authorship fraud (Teixeira da Silva, 2023), the interoperability with other databases and automatic updating of profiles by other entities in the research ecosystem (such as institutions, publishers, and funders) could significantly improve the completeness of metadata, thereby increasing the reliability of ORCID to carried out this type of studies (Teixeira da Silva, 2022;Bordons et al, 2024).…”
Section: Discussionmentioning
confidence: 99%
“…To date, we know that in Spain, found that the ORCID identifier is included in most articles published in Q1 and Q2 Spanish open access journals, with a predominant presence in Q1 journals, and that the Spanish National Research Council (CSIC) is the leading Spanish scientific publisher that has adopted it in its editorial management, suggesting that the ORCID identifier could become a criterion for editorial quality (Martínez Méndez & López Carreño (2019). Bordons et al (2024) analyzed ORCID adoption in Spanish scientific articles and among ERC grant recipients in Spain. They found that almost 90% of articles list at least one ORCID ID, but only 14% include ORCID IDs for all authors.…”
Section: Orcid Integrationmentioning
confidence: 99%
See 1 more Smart Citation